Utilising Cultural Heritage to Improve Water Security and Agro- Pastoral Farming in the Peruvian Andes - Lane, Kevin John (2025)
Across the Peruvian Andes, the significance and value of high-altitude wetlands (lakes, peatlands, and wet meadows over 2500 m a.s.l.) and their associated water management infrastructure (e.g. micro- dams) should not be underestimated.For millennia, these have provided an essential contribution to a range of ecosystem services, especially as a source of water for cultivation and highly nutritious grazing land for animals, in addition to sequestering carbon, regulating waterflow and enhancing biodiversity. Farming communities, and non- governmental organisations (NGOs) working with communities, recognise their importance and play an essential role in their management and conservation. Threats to wetlands due to climate change, including loss of glacier meltwater recharge, as well as drainage, conflict and mining, are well recognised. As such, these threats pose a considerable concern for water security and agro- pastoral farming.In this study, we summarise past and present water management in the Peruvian Andes and then undertake two case studies of wetlands and their associated water management infrastructure located in central Peru. The first is Antaycocha (Chillón valley, Lima Region), where we demonstrate how palaeoecology can be used to inform about the timing and role of dam construction and associated socio- economic change during the last 3000 years. Our second studyconcerns Ricococha Alta (Cordillera Negra, Ancash Region) where we demonstrate the contribution of indigenous knowledge and community engagement in dam restoration for protecting cultural heritage and sustainable development inthe context of climate change. These studies show how a blend of knowledge from cultural heritage, palaeoecology and indigenous communities can be used to better understand human– wetland interactions and provide know- how to informapproaches to sustainable rural development.